1994
DOI: 10.1002/mrd.1080380317
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of hamster epididymal sperm motility and influence of the thiol status of hamster and rat spermatozoa on their motility patterns

Abstract: A method for objective quantification of hamster sperm movement parameters as an indicator of maturation along the epididymis was established using a computerised system. Analysis of spermatozoa released into medium from five epididymal regions showed that the most drastic increases in percentage motility and curvilinear velocity (VCL) occurred from the distal corpus to the beginning of the proximal cauda and in straight-line velocity (VSL) from the beginning to a more distal site within the proximal cauda reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Sulfhydryl groups of sperm membrane proteins maintain a dynamic equilibrium with their disul®des counterparts (Calvin et al, 1973). Oxidation of sulfhydryl groups is associated with the acquisition of fertilizing ability of spermatozoa (Yeung et al, 1994). In rat epididymis, caput ligation caused an oxidation of sperm sulfhydryl groups triggering an early maturation of the gametes as evidenced by the acquisition of motility and of a partial increase in fertilizing ability (Seligman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfhydryl groups of sperm membrane proteins maintain a dynamic equilibrium with their disul®des counterparts (Calvin et al, 1973). Oxidation of sulfhydryl groups is associated with the acquisition of fertilizing ability of spermatozoa (Yeung et al, 1994). In rat epididymis, caput ligation caused an oxidation of sperm sulfhydryl groups triggering an early maturation of the gametes as evidenced by the acquisition of motility and of a partial increase in fertilizing ability (Seligman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…After attaining their maximal percentage motility and progressive velocity, slight but consistent decreases in motility of spermatozoa from the most distal epididymal region have been observed in hamsters and rats (Yeung et al, 1992(Yeung et al, , 1994b and are most obvious in men with prostatic carcinoma , probably due to the ageing of stored spermatozoa. In the present study this phenomenon of a decrease in percentage motility was only observed in the epididymis of one cynomolgus monkey.…”
Section: Discussionmentioning
confidence: 77%
“…The conditions and parameter set up values for the use of HTM-S Motility Analyzer for the analysis of hamster spermatozoa was as described earlier (Girija Devi and Shivaji, 1994) and was validated according to the guidelines of the HTM-S manual and as recom- mended by Yeung et al (1992) and Working and Hurtt (1987). A recent study has demonstrated that the settings validated for the analysis of rat spermatozoa also could be used for the analysis of hamster spermatozoa since these spermatozoa are very similar in size and shape (Yeung et al, 1994). The settings used in our previous study and in the present for hamster spermatozoa overlap with that reported by Yeung et al (1994) but are not identical.…”
Section: Discussionmentioning
confidence: 99%
“…With this in view, attempts had been made to standardize computer-aided methods for motility analysis of spermatozoa from humans (Robertson et al, 1987;Mack et al, 1988;Tesarik et al, 1990;Burkman, 1991), bull (Anzar et al, 1991), ram (Amann et al, 1982), and rat (Working and Hurtt, 1987;Slott et al, 1991;Yeung et al, 1992). Recently, a computer-aided motility analysis of hamster spermatozoa during maturation was described by us (Girija Devi and Shivaji, 1994) and the results were confirmed by Yeung et al (1994), who used a videorecording apparatus and the computer aided motion analysis system HTM 2030.…”
Section: Comparison Of the Distribution Of Hamster Spermatozoa Exhibimentioning
confidence: 98%